Analisis Penerimaan Dan Penggunaan Aplikasi JMO Mobile Di PT Basirih Industrial Menggunakan Model UTAUT 2 - Mahendra, Muhammad (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
The development of information technology in the era of the digital revolution has changed the way organizations and companies operate. The utilization of information technology has become the key to improving business effectiveness, efficiency, and competitiveness. However, success in the adoption of information technology does not only depend on technical aspects alone, but is also influenced by the attitudes and behaviors of technology users. This study uses the UTAUT 2 Model and SmartPLS 3.2.9 analysis to understand the factors that influence the acceptance and use of the JMO Mobile application at PT Basirih Industrial. The results of the analysis show that factors such as performance expectations, social influence, hedonic motivation, and habit have a significant role in shaping the intention and behavior of using the application. These findings provide valuable insights for companies in increasing the adoption of information technology in their work environment, so that they can effectively utilize information technology in the face of change and competition in the ever-evolving digital era.